Resolution of 1,3-dioxolane derivatives using the lipase from an Acinetobacter junii SY-01 - Moon-Young, Y; Lee, SH; Cheong, CS; Park, JK (ELSEVIER SCIENCE INC, 2004)
Acinetobacter junii SY-01 producing a lipase enantioselectively hydrolyzing 1,3-dioxolane derivatives was isolated from water sludge sample and the effect of solvent, acyl donor, vinyl acetate concentration, substrate concentration, operating temperature and immobilization on activity and enantioselectivity was studied for the resolution of 1,3-dioxolane derivatives through transesterification reaction using a lipase from the isolated strain. Best selectivity was obtained at lower substrate concentration (3-5 mM), higher vinyl acetate concentration (500-1000 mM) and lower temperature (30-40degreesC) in the reaction mixture. Lipase immobilized onto Accurel MP-1000 (micro-porous polypropylene) gave the best results and the reactivity was about 29-fold higher than the free enzyme without the decrease of enantioselectivity. Resolution of 1,3-dioxolane derivatives was carried out in flask scale containing 100 ml solvents using the lipase immobilized onto Accurel MP-1000. In this reaction, the yield and enantiomeric excess of the remaining (2R, 4S)-alcohol were 31.2% and 98.2%, respectively. This result suggests that it can be used as an alternative method, compared to the present synthetic method, for the production of optically pure (2R, 4S)-itraconazole. (C) 2004 Published by Elsevier Inc.
Keywords: CHIRAL DRUGS; ENZYMES